Mechanism and Prediction of Geothermal Resources Controlled by Neotectonics in Mountainous Areas: A Case Study of Southeastern Zhangjiakou City, China - Yuan, Wenzhen; Lei, Xiaodong; Liu, Tongzhe; Wang, Siqi; Xing, Yifei; Zhu, Ruijie; Yang, Fengtian; Zhang, Dailei; Gao, Jun; Zhang, Baojian (Frontiers in Earth Science, 2022)
The geothermal resources in mountainous areas are usually controlled by neotectonic faults. To minimize the risk in site selection for geothermal drilling, the controlling mechanism must be identified. Based on the neotectonic control theory for geothermal resources, the occurrence of the geothermal resources in the mountainous area in southeastern Zhangjiakou city was investigated. The investigation was divided into three stages. Firstly, field investigation for neotectonics was carried out to characterize the kinematics and the stress state of the faults, including fault occurrences, tectonic stages and paleostress analysis, and in total 19 nectectonic faults were confirmed. Based on Riedel shear model and present stress field, their conductivity for geothermal water was inferred; Secondly, geophysical and geochemical surveys were applied to identify the stress state and characterize the occurrence of the potential water conductive faults. The results showed that the combine use of MT, CSAMT and 2D seismologic survey is effective in delineating fault occurrence, strata distribution and water conductivity within 1000 m depth, while measurement of 222Rn activity in soil gas across the neotectonic faults is effective to investigate the groundwater conductivity of the faults, and all the neotetonic faults in the study area strikes clockwise from N5E to N25W are considered to be water conductive, thus the areas at the intersection zones of neotetonic faults in the basin in groundwater runoff and discharge regions are promising targets for geothermal exploration. This conceptual model was verified by the geothermal fields already discovered in the study area and proved to be reasonable, and then a potential drilling site was predicted and proved to be successful. It is suggested that this workflow for geothermal exploration is suitable for Zhangjiakou city, and may also be applied to other mountainous areas.